Understanding placental nutrient transfer – why bother? New biomarkers of fetal growth - Sibley, C P (Blackwell Science Inc, 2009)
The placenta, in general and the physiology of maternofetal nutrient transfer is under-researched compared to other organs with epithelial transport function, as evidenced, for example, by publication numbers. This report provides reasons why more researchers should become involved in this topic. First, the syncytiotrophoblast, the transporting epithelium of the placenta, though having many basic cell physiology properties similar to those of other transporting epithelia, has several properties which are markedly different. Better information on these might help fundamental understanding of how epithelia in general function as well as improving knowledge of how the syncytiotrophoblast operates. Second, the synctiotrophoblast has a key role in controlling fetal growth, not only by transporting nutrients and waste products of metabolism but also because it increasingly appears to be one site, perhaps even the dominant site, in which integration of, sometimes conflicting, signals between mother and fetus takes place. Finally, better understanding of placental nutrient transfer and especially of how it is regulated by maternal and fetal signals could provide better information on the placental phenotype in fetal growth disorders – information which might contribute to providing better biomarkers which the obstetrician could use to improve early diagnosis of these disorders.